Exploring dual-coating strategies for probiotic microencapsulation using polysaccharide and protein systems - Sin, Phin Yin; Tan, Suat Hian; Mohd Fazli, Farida Asras; Lee, Chin Mei; Lee, Thong Chuan; Karim, Md. Rezaul; Ma, Nyuk Ling (Springer Nature, 2025)
Probiotics are known for their significant health benefits, contributing to improved gut health and overall well-being. Despite their potential, maintaining their viability during processing, storage, and gastrointestinal transit remains a major challenge. Meanwhile, current microencapsulation techniques often rely on single biopolymers such as polysaccharides or proteins, which are insufficient for comprehensive protection. Polysaccharides form gel-like matrices that shield probiotics from acidic and oxidative stress but lack adequate mechanical strength. Conversely, proteins offer structural stability and emulsifying properties but are less resistant to extreme environmental conditions. These limitations highlight the need for innovative delivery systems. Dual-coating microencapsulation, combining polysaccharides and proteins, has emerged as a promising solution. Polysaccharide–polysaccharide systems enhance gastrointestinal protection through robust gel-like matrices formed via ionic and hydrogen bonding. Protein–polysaccharide systems exploit the complementary properties of both materials, with proteins offering structural support and buffering capacity while polysaccharides enhance stability and control release. These synergistic interactions significantly improve probiotic viability and functionality under extreme conditions. This review examines the mechanisms, benefits, and challenges of dual-coating strategies. Key challenges include strain compatibility, regulatory complexities, and the scalability of manufacturing processes. Future research should focus on advanced techniques like layer-by-layer assembly for precise control of coating layers. Additionally, molecular omics technologies can unravel strain interactions within multi-strain formulations, optimizing encapsulation systems. The integration of sustainable, biocompatible materials into cost-effective processes is critical for commercial success. By addressing these challenges, dual-coating microencapsulation can revolutionize probiotic delivery systems, advancing functional foods and therapeutic applications to promote human health and well-being.